CONSTRUCTING A PSYCHOLOGICAL EXHAUSTION SCALE FOR IRAQI PREMIER LEAGUE FOOTBALL CLUBS AND ITS RELATIONSHIP TO NEGATIVE EMOTIONAL BEHAVIOR FOR 2024-2025 SPORTS SEASON - Maitham Mutair Hamidi Al-Krizi (Universitas Negeri Jakarta, 2025)
Background. The Iraqi Premier League has witnessed great interest in the recent period, by the Iraqi Central Football Association in general and sports clubs in particular, by summoning the best players, from various local, Arab and international clubs, despite the high costs spent on professional players, for the purpose of advancing their clubs. Objectives. The research aims to build a scale of psychological exhaustion and a scale of negative emotional behavior for some players of Premier League football clubs and to find relationship between them. Method. The descriptive approach was used with sample method. The exploratory study was applied to a sample of ( 21 ) players and main study was applied to ( 121 ). Appropriate statistical treatments were used on ( 6 ) sources (anxiety - tension - pessimism - frustration - distraction - psychological pressure), which represent main sources of psychological exhaustion scale after presenting them to the experts, numbering ( 12 ) experts. These became main sources of psychological exhaustion scale, which consists of ( 48 ) phrases, as they were presented to the experts, with ( 8 ) phrases for each source, and two phrases were deleted for each source. Thus, the scale of sources of psychological exhaustion consists of ( 36 ) phrases, with ( 6 ) phrases for each source, and scale of negative emotional behavior consists of ( 28 ) phrases. Results. It is noted from results for scale of sources of psychological exhaustion for players of some Premier League football clubs that coefficient reached (0.823), which indicates that phrases are characterized by very good validity and reliability, as phrases of scale reached (36) phrases. It is also coefficient for the scale of negative emotional behavior reached (0.857), which indicates that phrases are characterized by high validity and reliability for scale of negative emotional behavior for players of Premier League football clubs, as phrases of emotional behavior scale reached (28) phrases. Conclusion. Players of some clubs Premier League football suffers from sources of psychological exhaustion and these sources can be used to measure psychological exhaustion among players, in addition to their negative emotional behavior.